Formulation and evaluation of lactic acid bacteria fermented Brassica juncea (Mustard Greens) pickle with cholesterol lowering property - Chaiyavat Chaiyasut (2018)
© 2018 Chaiyavat Chaiyasut et al. Lactic acid bacteria (LAB) mediated fermented mustard green (MG) pickle was prepared, and the cholesterol-lowering property of the pickle was evaluated. LAB strains were isolated by a plating method and biochemically characterized. Pickle formula was prepared with a various combination of seasonings. Lactic, and acetic acid content was assessed by high-performance liquid chromatography. Methanol and ethanol contents were estimated by gas chromatography. The antimicrobial property was evaluated by plate assay. Cholesterol content was detected by the o-phthalaldehyde method. About 373 bacterial isolates were isolated. After the selection process (bile and pH tolerance, bile salt hydrolase activity, biochemical profile, and growth pattern), isolate LAB5 was selected as a starter for pickle formulation. Twenty-seven different pickle formulas were prepared. Lactic acid content increased gradually, whereas acetic acid level decreased in the pickles. The acceptable level of ethanol was observed in pickles after 30 days with no methanol content. Pickles showed antimicrobial activity against tested microbes. Cholesterol level in pickle liquid was reduced significantly. The stability and sensory analysis suggested that pickle formula-2 was accepted by the healthy volunteers. LAB5 fermented MG pickle could be a functional food to control cholesterol. Additional clinical trial helps to explore the in vivo cholesterol lowering property of the formulated pickle.